Differentiation Questions

Question Number 196209 by mnjuly1970 last updated on 19/Aug/23

$$\\$$$$\:\:\:\:\:\:\Omega=\:\int_{\mathrm{0}} ^{\:\mathrm{1}} \frac{\:\left({x}−\mathrm{1}\right)^{\:\mathrm{2}} }{\mathrm{ln}^{\mathrm{2}} \left({x}\right)}\:{dx}=\:? \\$$$$\:\:\:\:\:−−−− \\$$

Answered by Mathspace last updated on 20/Aug/23

$${lnx}=−{t}\:\Rightarrow\Phi= \\$$$$\\$$$$\int_{\mathrm{0}} ^{\infty} \frac{\left({e}^{−{t}} −\mathrm{1}\right)^{\mathrm{2}} }{{t}^{\mathrm{2}} }{e}^{−{t}} {dt} \\$$$$=\int_{\mathrm{0}} ^{\infty} \:\frac{{e}^{−{t}} \left({e}^{−\mathrm{2}{t}} −\mathrm{2}{e}^{−{t}} +\mathrm{1}\right)}{{t}^{\mathrm{2}} }{dt} \\$$$$=\int_{\mathrm{0}} ^{\infty} \:\frac{{e}^{−\mathrm{3}{t}} −\mathrm{2}{e}^{−\mathrm{2}{t}} +{e}^{−{t}} }{{t}^{\mathrm{2}} }{dt} \\$$$$=\left[−\frac{\mathrm{1}}{{t}}\left({e}^{−\mathrm{3}{t}} −\mathrm{2}{e}^{−\mathrm{2}{t}} +{e}^{−{t}} \right)\right]_{\mathrm{0}} ^{\infty} \\$$$$+\int_{\mathrm{0}} ^{\infty} \:\frac{\mathrm{1}}{{t}}\left(−\mathrm{3}{e}^{−\mathrm{3}{t}} +\mathrm{4}{e}^{−\mathrm{2}{t}} −{e}^{−{t}} \right){dt} \\$$$$=\lambda_{\mathrm{0}} −\int_{\mathrm{0}} ^{\infty} \frac{\mathrm{3}{e}^{−\mathrm{3}{t}} −\mathrm{4}{e}^{−\mathrm{2}{t}} +{e}^{−{t}} }{{t}}{dt} \\$$$${with}=\lambda_{\mathrm{0}} ={lim}_{{t}\rightarrow\mathrm{0}} \frac{{e}^{−\mathrm{3}{t}} −\mathrm{2}{e}^{−\mathrm{2}{t}} +{e}^{−{t}} }{{t}} \\$$$$={lim}_{{t}\rightarrow\mathrm{0}} \frac{−\mathrm{3}{e}^{−\mathrm{3}{t}} +\mathrm{4}{e}^{−\mathrm{2}{t}} −{e}^{−{t}} }{\mathrm{1}}\left({hospital}\right) \\$$$$=\mathrm{0}\:\Rightarrow \\$$$${I}=−\int_{\mathrm{0}} ^{\infty} \:\:\frac{\mathrm{3}{e}^{−\mathrm{3}{t}} −\mathrm{4}{e}^{−\mathrm{2}{t}} +{e}^{−{t}} }{{t}}{dt} \\$$$${we}\:{consider}\:\varphi\left(\lambda\right)=\int_{\mathrm{0}} ^{\infty} \frac{\left(\mathrm{3}{e}^{−\mathrm{3}{t}} −\mathrm{4}{e}^{−\mathrm{2}{t}} +{e}^{−{t}} \right){e}^{−\lambda{t}} }{{t}}\:\left(\lambda>\mathrm{0}\right) \\$$$$\varphi'\left(\lambda\right)=−\int_{\mathrm{0}} ^{\infty} \left(\mathrm{3}{e}^{−\mathrm{3}{t}} −\mathrm{4}{e}^{−\mathrm{2}{t}} +{e}^{−{t}} \right){e}^{−\lambda{t}} {dt} \\$$$$=−\mathrm{3}\int_{\mathrm{0}} ^{\infty} {e}^{−\left(\mathrm{3}+\lambda\right){t}} {dt}+\mathrm{4}\int_{\mathrm{0}} ^{\infty} {e}^{−\left(\mathrm{2}+\lambda\right){t}} {dt} \\$$$$−\int_{\mathrm{0}} ^{\infty} {e}^{−\left(\mathrm{1}+\lambda\right){t}} {dt} \\$$$$=\left[\frac{−\mathrm{1}}{\mathrm{3}+\lambda}{e}^{−\left(\mathrm{3}+\lambda\right){t}} \right]_{\mathrm{0}} ^{\infty} +\mathrm{4}\left[−\frac{\mathrm{1}}{\mathrm{2}+\lambda}{e}^{−\left(\mathrm{2}+\lambda\right){t}} \right]_{\mathrm{0}} ^{\infty} \\$$$$−\left[−\frac{\mathrm{1}}{\mathrm{1}+\lambda}\:{e}^{−\left(\mathrm{1}+\lambda\right){t}} \right]_{\mathrm{0}} ^{\infty} \\$$$$=\frac{\mathrm{1}}{\mathrm{3}+\lambda}+\frac{\mathrm{4}}{\mathrm{2}+\lambda}−\frac{\mathrm{1}}{\mathrm{1}+\lambda}\:\Rightarrow \\$$$$\varphi\left(\lambda\right)={ln}\left(\lambda+\mathrm{3}\right)+\mathrm{4}{ln}\left(\lambda+\mathrm{2}\right)−{ln}\left(\lambda+\mathrm{1}\right)\:+{c} \\$$$$\Rightarrow{I}=−{lim}_{\lambda\rightarrow\mathrm{0}} \varphi\left(\lambda\right) \\$$$$=−{ln}\mathrm{3}−\mathrm{4}{ln}\mathrm{2}−{c} \\$$$$−\varphi\left(\lambda\right)=−{ln}\left(\lambda+\mathrm{3}\right)−\mathrm{4}{ln}\left(\lambda+\mathrm{2}\right)+{ln}\left(\lambda+\mathrm{1}\right)−{c} \\$$$$={ln}\left(\frac{\lambda+\mathrm{1}}{\lambda+\mathrm{3}}\right)+{ln}\left(\frac{\mathrm{1}}{\left(\lambda+\mathrm{2}\right)^{\mathrm{4}} }\right)\:\Rightarrow \\$$$${lim}−\varphi\left(\lambda\right)=−{c}=\mathrm{0}\:\Rightarrow \\$$$${I}=−{ln}\mathrm{3}−\mathrm{4}{ln}\mathrm{2}...! \\$$$${perhaps}\:{there}\:{is}\:{arror}\:{of}\:{sign}? \\$$

Commented by mnjuly1970 last updated on 20/Aug/23

$$\: \\$$

Answered by witcher3 last updated on 20/Aug/23

$$\Omega=\int_{\mathrm{0}} ^{\mathrm{1}} \frac{\mathrm{x}\left(\mathrm{x}−\mathrm{1}\right)^{\mathrm{2}} }{\mathrm{xln}^{\mathrm{2}} \left(\mathrm{x}\right)}\mathrm{dx} \\$$$$\mathrm{u}=\mathrm{x}\left(\mathrm{x}−\mathrm{1}\right)^{\mathrm{2}} ,\mathrm{u}'=\left(\mathrm{x}−\mathrm{1}\right)^{\mathrm{2}} +\mathrm{2x}\left(\mathrm{x}−\mathrm{1}\right),\mathrm{v}'=\frac{\mathrm{1}}{\mathrm{xln}^{\mathrm{2}} \left(\mathrm{x}\right)} \\$$$$\mathrm{v}=−\frac{\mathrm{1}}{\mathrm{ln}\left(\mathrm{x}\right)} \\$$$$. \\$$$$\Omega=\underset{\left(\mathrm{a},\mathrm{b}\right)\rightarrow\left(\mathrm{0},\mathrm{1}\right)} {\mathrm{lim}}\left[−\frac{\left(\mathrm{x}−\mathrm{1}\right)^{\mathrm{2}} }{\mathrm{ln}\left(\mathrm{x}\right)}\right]_{\mathrm{a}} ^{\mathrm{b}} +\int_{\mathrm{0}} ^{\mathrm{1}} \frac{\left(\mathrm{x}−\mathrm{1}\right)\left(\mathrm{3x}−\mathrm{1}\right)}{\mathrm{ln}\left(\mathrm{x}\right)} \\$$$$=\int_{\mathrm{0}} ^{\mathrm{1}} \frac{\mathrm{x}−\mathrm{1}}{\mathrm{ln}\left(\mathrm{x}\right)}.\left(\mathrm{3x}−\mathrm{1}\right)\mathrm{dx} \\$$$$\int_{\mathrm{0}} ^{\mathrm{1}} \left(\mathrm{3x}−\mathrm{1}\right)\int_{\mathrm{0}} ^{\mathrm{1}} \mathrm{x}^{\mathrm{t}} \mathrm{dtdx} \\$$$$=\int_{\mathrm{0}} ^{\mathrm{1}} \int_{\mathrm{0}} ^{\mathrm{1}} \left(\mathrm{3x}−\mathrm{1}\right)\mathrm{x}^{\mathrm{t}} \mathrm{dxdt} \\$$$$\int_{\mathrm{0}} ^{\mathrm{1}} \int_{\mathrm{0}} ^{\mathrm{1}} \mathrm{3x}^{\mathrm{t}+\mathrm{1}} −\mathrm{x}^{\mathrm{t}} \mathrm{dxdt} \\$$$$=\int_{\mathrm{0}} ^{\mathrm{1}} \frac{\mathrm{3}}{\mathrm{t}+\mathrm{2}}−\frac{\mathrm{1}}{\mathrm{t}+\mathrm{1}}=\mathrm{3ln}\left(\mathrm{3}\right)−\mathrm{3ln}\left(\mathrm{2}\right)−\mathrm{ln}\left(\mathrm{2}\right) \\$$$$=\mathrm{3ln}\left(\mathrm{3}\right)−\mathrm{4ln}\left(\mathrm{2}\right) \\$$$$\\$$$$\\$$